Evaluation of the Neurohormonal System in Patients with Chronic Heart Failure Characterized by Postinfarction Cardiosclerosis (Eurasian Research Bulletin, 2023)
A total investigation of 115 patients. Chronic heart failure (CHF) of the 1-st functional class (FC) was found in 19 patients (16.5%), 2-nd FC in 48 patients (41.8%), 3-d FC in 40 (34.7%) and 4-th FC in 8 (6.9%). In their peripheral venous blood plasma norepinephrine, aldosterone and brain natriuretic peptide were investigated. The amount of N in patients with cardiosclerosis post infarction increased in the 2-d, 3-d and 4-th FC; A increased in all the groups and with normal (FV) and didn’t depend on diastolic or systolic kind of CHF. The amount of BNP also increased with the appearance of systolic heart insufficiency and grew as the level of CHF increased . The BNP level can be a diagnostic test for a low FC's grade of CHF.